Correlation of Vitamin D3 Level and Periodontal Health - Abbas, Aliza; Ashraf, Muhammad Sharjeel; Ali, Asma Wahid; Ahmed, Yasir Ikram; Fatima, Natasha; Tanvir, Syed Adil (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine whether periodontitis severity, complexity, and progression risk are associated with variations in vitamin D3 levels, providing insights into potential links between this essential nutrient and periodontal health. Study Design: Comparative cross sectional study Place and Duration of Study: Armed forces Institute of Dentistry (AFID), Rawalpindi Pakistan, from Mar to Oct 2024. Methodology: Two hundred and eighty individuals were included. Participants were categorized into two groups (Group-A included 140 individuals with a healthy periodontium and Group-B had 140 diagnosed with periodontitis). Clinical attachment loss (CAL), probing pocket depth (PPD), and bleeding on probing (BOP) were taken as a measure of periodontal clinical parameters. Vitamin D3 concentration in serum was tested by 25-hydroxy vitamin D (25(OH)D) test after attained radiographs. Results: Between healthy and patients with periodontitis, the differences were found to be significant for PPD, CAL, BOP, and serum vitamin D₃ levels. Median vitamin D₃ levels progressively reduced as the stage and grade of periodontitis increased (41.5 ng/mL in Stage 1 to 20.5 ng/mL in Stage 4) and (41.6 ng/mL in Grade A to 24.1 ng/mL in Grade C). Vitamin D₃ was inversely related to CAL (r = –0.658), PPD (r = –0.487), BOP (r = –0.658), and BMI (r = –0.140). Regression indicated that CAL was the most predictive of vitamin D deficiency. Conclusion: Serum D3 levels of vitamin have a significant association with periodontitis disease.